Acceptance of arabic and direction of jawi script : an outlook from youth perspective - Nur Azuki Yusuff; Siti Bahirah Saidi (2014)
Direction of Arabic and development of Jawi script should be in accordance with the need and priority in mastering them. This need is seen through different dimensions. Youth nowadays look at the acceptance towards Arabic as having close relationship with the Islamic practice and its relevance to economic, social and world politics. The upholders of Arabic and Jawi script are both religious people and general society. Three areas of discussion in this paper are; the challenge faced by Arabic and Jawi script, the difference in their use, and the strategies to ensure their sustainability.